2016
DOI: 10.1371/journal.pone.0153411
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Tumor Heterogeneity, as Evidenced by Gene Expression Profiles, Pathway Activation, and Gene Copy Number, in Patients with Multifocal Invasive Lobular Breast Tumors

Abstract: BackgroundInvasive lobular carcinoma (ILC) comprises approximately ~10–20% of breast cancers. In general, multifocal/multicentric (MF/MC) breast cancer has been associated with an increased rate of regional lymph node metastases. Tumor heterogeneity between foci represents a largely unstudied source of genomic variation in those rare patients with MF/MC ILC.MethodsWe characterized gene expression and copy number in 2 or more foci from 11 patients with MF/MC ILC (all ER+, HER2-) and adjacent normal tissue. RNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 45 publications
1
38
0
Order By: Relevance
“…Because alterations in genome and epigenome profiles often lead to heterogeneous gene expression profiles in tumors, defining ITH based on gene expression profiles is a viable approach 21 23 . Park et al proposed a method (tITH) for evaluating transcriptome-based ITH using RNA-Seq data 24 .…”
Section: Introductionmentioning
confidence: 99%
“…Because alterations in genome and epigenome profiles often lead to heterogeneous gene expression profiles in tumors, defining ITH based on gene expression profiles is a viable approach 21 23 . Park et al proposed a method (tITH) for evaluating transcriptome-based ITH using RNA-Seq data 24 .…”
Section: Introductionmentioning
confidence: 99%
“…Signals included are COL1A1, COL11A1, SPP1, COMP, SFRP4, and INHBA. Numerous studies have shown the proliferative role of collagen in gastric 32,36 , breast 37 , and colon cancers 38,39 . Previous studies have also demonstrated that the upregulation of MMPs (MMP7 and 9) along with other collagen proteins are important for tumor vascular invasion 40 .…”
Section: Discussionmentioning
confidence: 99%
“…These variations in gene expression might be related to intrinsic factors that are connected to platform efficiency and the process of direct detection without the need of amplification in the NS platform, but which are needed for preamplification on the FD platform. 17 , 27 , 28 …”
Section: Discussionmentioning
confidence: 99%
“… 14 , 15 Recently, a new platform for low-throughput gene expression based on molecular barcoding to quantify mRNA that does not require amplification has become available. 16 , 17 , 18 Previous studies have favorably compared the barcoded-oligo assay to QPCR in other clinical settings 19 , 20 Recently, a study by Adam et al. quantified the expression of a literature-derived, antibody-mediated rejection 34-gene panel in fresh-preserved and FFPE kidney tissues with QPCR and the barcoded-oligo assay, respectively.…”
mentioning
confidence: 99%